A model for developing dependable system using component-based software development approach / Hasan Kahtan Khalaf Al-Ani - Khalaf Al-Ani, Hasan Kahtan (Institute of Graduate Studies, UiTM, 2014)
Component-based software development (CBSD) is an emerging technology that focuses on building systems by integrating existing software components. The software industry has adopted CBSD to rapidly build and deploy large and complex software systems with enormous savings despite minimal engineering effort, cost, and time. CBSD provides several benefits, such as improved ability to reuse existing codes, reduced development costs of high-quality systems, and shorter development time. However, CBSD encounter issues in terms of security trust mainly in dependability attributes. A system is considered dependable when it can be depended on to produce the consequences for which it was designed, with no adverse effect in its intended environment. Dependability comprises several attributes that imply availability, confidentiality, integrity, reliability, safety, and maintainability. Embedding dependability attributes in CBSD is essential for developing dependable component software.